The Development of an Information System for Tracking Research Funding within the Faculty of Pharmacy, Mahasarakham University - Nindee, Kanungsri (Kalasin University Journal of Science Technology and Innovation, 2025)
The purposes of this study were: (1) to develop an information system for tracking research funding; (2) to evaluate the efficiency of the system; and (3) to examine user satisfaction within the Faculty of Pharmacy, Mahasarakham University. The research followed the seven phases of the System Development Life Cycle (SDLC): problem definition, analysis, design, development, testing, implementation, and maintenance. The sample consisted of 46 administrators, lecturers, and staff members, selected from a total population of 60. The research instruments included: (1) the developed information system for tracking research funding; (2) a system quality evaluation form; (3) a system efficiency evaluation form; and (4) a user satisfaction questionnaire.The results revealed that: experts evaluated the quality of the system at the highest level, users evaluated the efficiency of the system at the highest level, and users reported the highest level of satisfaction with the system respectively.